Photodetectors: A Broadband Fluorographene Photodetector (Adv. Mater. 22/2017). Issue 22 (7th June 2017) - Du, Sichao; Lu, Wei; Ali, Ayaz; Zhao, Pei; Shehzad, Khurram; Guo, Hongwei; Ma, Lingling; Liu, Xuemei; Pi, Xiaodong; Wang, Peng; Fang, Hehai; Xu, Zhen; et al.
Abstract : Graphene can be used for wide‐broadband photodetectors since its photoresponse spectrum covers from the UV to the terahertz frequencies. A graphene hyperspectral image of West‐Lake in Hangzhou, China is shown, indicating the wealth of sufficient information held in the broad spectral domain. The work described in article number1700463 by Yang Xu, Weida Hu, and co‐workers shows potential application in, for example, global climate research, mapping of wetlands, mineral identification, crop analysis, and bathymetry.